Improve the quality of life with magnetically implant-supported overdenture - Darmiaty; Sitti Arfa; Edy Machmud; Ike Damayanti Habar (Indonesia Prosthodontic Association, 2022)
A 50-year-old female came to Hasanuddin University Dental Hospital Makassar with chief complaint of masticatory problems due to a denture that had been used for 9 years was loose, causing pain when eating. Intra-oral examina-tion showed that the patient is completely edentulous. The mandibular alveolar ridge had resorbed. The patient was treated with an implant-supported overdenture with magnetic retention in the mandible. The maxilla is treated with conventional denture as there was still part of the maxilla that could be used for retention. After obtaining the pati-tient's consent and confirming that the patient had no parafunction, two implants were placed on the body of the mandible using single stage implants. Right and left implants were 12.0 mm long and 4.0 mm diameter. Both the magnet and the attachment shield were coated with titanium nitride (TiN). It is concluded that magnetically implant-supported overdenture can restore masticatory function and the quality of life.